Frequency of Post-Thyroidectomy Hypoparathyroidism in Surgical Patients: Post-Thyroidectomy Hypoparathyroidism in Surgical Patients - Shoukat, Hassan; Ahmad, Hafiz Ashfaq; Kazmi, Abbas Hassnain; Rasheed, Kiran Abdul; Mukhtar, Nasir; Shahid, Madeeha; Qasim, Tuba Binte (Pakistan Journal of Health Sciences, 2026)
The risk of post-operative hypoparathyroidism is increased after thyroidectomy. It can be transient or permanent, potentially leading to severe neuromuscular and respiratory complications. Objectives: To identify postoperative hypoparathyroidism based on serum post-thyroidectomy hypoparathyroidism (PTH) levels after total thyroidectomy. Methods: This was a cross-sectional study, conducted after total thyroidectomy on 88 participants at the Department of Surgery, Niazi Welfare Foundation Teaching Hospital, Sargodha, from 1st October, 2024 to 30th November, 2025. Patients with an age range of 22 to 62 years undergoing total thyroidectomy were included in this study, while others with hyperparathyroidism, a history of neck radiotherapy, preoperative hypocalcemia, or preoperative suspicion of malignancy were excluded. A predesigned form was used to collect data regarding demographics, personal habits, comorbidities, reasons for performing total thyroidectomy, and postoperative hypoparathyroidism. Serum PTH level of <10 pg/ml was marked as diagnostic criteria for postoperative hypoparathyroidism. SPSS version 26.0 was used to analyze data. Results: In this Study, out of 88 participants, there were 25 male patients and 63 females. The patients' ages ranged from 22 to 62 years, with a mean age of 40.56 ± 8.23 years. 30 participants belong to the age group of 22-42 years, whereas 58 participants were in the age range of 43 to 62 years. Post-operative hypoparathyroidism was revealed in 19 (21.59%) participants. Conclusions: Postoperative hypoparathyroidism was observed in the majority of patients after total thyroidectomy.